Microenvironment commits breast tumor ECs to dedifferentiation by micro-RNA-200-b-3p regulation and extracellular matrix remodeling - Wilkus-Adamczyk, Kinga; Brodaczewska, Klaudia; Majewska, Aleksandra; Kieda, Claudine (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Hypoxia shapes the tumor microenvironment, modulates distinct cell populations activity and activates pathological angiogenesis in cancer, where endothelial cells (ECs) are the most important players. The study aim was to evidence the tumor microenvironment influences on the global gene expression pattern characteristic for ECs and evidence the distinct responses displayed by the tumor-derived ECs compared to the healthy endothelium during the endothelial to mesenchymal transition (EndMT) and its regulation by miR-200-b-3p. Methodology: Immortalized lines of ECs from the same patient with breast cancer, healthy breast tissue (HBH.MEC) and primary tumor (HBCa.MEC), were used. The experiments were performed in normoxia and hypoxia for 48 hours. By wound healing test, we investigated the migration abilities of ECs. Global gene expression analysis with NGS was carried out to detect new pathways altered in pathological ECs and to find the most changed miRNAs. The validation of NGS data from RNA and miRNA was estimated by qPCRs. Mimic miR-200b-3p was used in HBH.MEC and the following targets were checked: VEGF, Bcl2, ROCK2 and SP1. Results: Hypoxia influences ECs migration properties in wound healing assay. In hypoxia, healthy ECs migrate slower than in normoxia, as opposed to HBCa.MEC where no decreased migration ability was induced by hypoxia, due to EndMT features. NGS data identified this process to be altered in cancer ECs through extracellular matrix (ECM) organization. The deregulated genes, validated by qPCR, included: SPP1, ITGB6, COL4A4, ADAMST2, LAMA1, GAS6, PECAM1, ELN, FBLN2, COL6A3, COL9A3. NGS also identified collagens, laminin, fibronectin and integrin, as being deregulated in tumor-derived ECs. Moreover, the analysis of ten most intensively modified miRNAs when breast tumor-derived ECs were compared to healthy ECs, put a light on miR-200b-3p which is strongly up-regulated in HBCa.MECs as compared to HBH.MECs. Discussion and Conclusions: The pathological ECs differed significantly, both phenotypically and functionally, from the normal corresponding tissue, thus influencing their microenvironment cross-talk. The gene expression profile confirms the EndMT phenotype of tumor-derived ECs and migratory properties acquisition. Moreover, it indicates the role of miR-200b-3p, regulating EndMT in pathological ECs, silencing several angiogenic growth factors and their receptors by directly targeting their mRNA transcripts.